High-Efficiency Ultra-Broadband Multi-Tip Edge Couplers for Integration of Distributed Feedback Laser With Silicon-on-Insulator Waveguide - Yi-Chou Tu; Po-Han Fu; Ding-Wei Huang (IEEE Photonics Journal, 2019)
A high-efficiency ultra-broadband multi-tip edge coupler based on a silicon-on-insulator platform for direct coupling with the elliptic beam of a distributed feedback laser was developed. The device is composed of a multi-tip section and a combiner section with extra offset regions to reduce the mode mismatch caused by the structural discontinuity which results from a limitation of the fabrication process that creates an inevitable gap width at the junction between the two sections. The widths and the spacing of the tips for the multi-tip section and the extra offset region for the combiner section are fine-tuned by using the particle swarm optimization method to reduce the mode mismatch. A high overall coupling efficiency up to 90.68% (0.4249 dB) at 1550 nm can be achieved for the optimized 90-μm-long four-tip edge coupler. The device can be operated over a broad spectral range of 1260–1675 nm with less than 1 dB extra loss. With its high-efficiency ultra-broadband operation and small device footprint, the proposed device is promising for laser-to-chip edge coupling in silicon photonics.